UNDERSTANDING CHINESE K?I AND GU?N WHEN REMINDING PEOPLE TO SWITCH MOBILE MODE - Wang, Chunying (International Journal of Language and Literary Studies, 2020)
This study investigates why people identically understand both Mandarin expressions ???????/q?ng ji?ng sh?u j? k?i zhèn dòng and???????/q?ng ji?ng sh?u j? gu?n zhèn dòng, which both mean please set your phone to vibrate. Four perspectives can be employed to explain. Firstly, the embodiments or imageries of ?/k?i/open and?/gu?n/close function in the expressions. However, only examining both expressions via imageries is insufficient to explain all the aspects. Relevance theory and the figure and ground relationship influence people’s selection of the expressions because the focus is different. Finally, people may directly connect the two actions k?i and gu?n to a single action, ?/àn/press, because of the development of touchscreen technology. Therefore, k?i and gu?n become similar under the context of reminding people to change their mobile into silent or vibration mode because no matter which expression is heard, the only action people have to do is to press or touch a specific icon on their smartphones.